Simplified description of the characteriscs of microstrip resonators with a ferrite component - Nurgaliev, T; Miteva, S; Stevens, C; Edwards, D (2004)
Relatively simple approximate formulas are proposed for describing of transmission characteristics of HTS microstrip resonator structures with a monocrystalline ferrite component and for describing of microwave losses in such structures, caused by magnetostatic waves. It was shown, that excitation of magnetostatic waves leads to a decrease of the quality factor and to a "distortion" of the transmission characteristics of the structure.